The Community of Da’wah and Dhikr Prayers in Shaping Socio-Religious Changes - Ika Fatmawati; Mohamed Ali Mohamed Yousef (Journal of Southern Sociological Studies, 2025)
Every individual or society must experience changes both in the community and family. The socio-religious changes that occurred in Hamlet II of Taman Fajar Village have an influence on the order of people's lives, because socio-religious changes through socio-religious activities are one of the activities that greatly support community life today, based on the phenomenon of community life, especially among children and adolescents who are increasingly distant from religious activities. The presence of Sholawat Da'wah and Dhikr which is a non-formal institution in the midst of the people of Taman Fajar Village, has made a very big contribution to the community because its main purpose is to teach things about religious teachings for members of the congregation and the community who participate in Sholawat Da'wah Dhikr activities which previously had minimal religious understanding. This research uses the field research method and the result of this research is the strategy of Sholawat Da'wah Dhikr through the socio-religious activities that they carry out in supporting socio-religious changes in the community which can be seen the changes today. The strategy that the congregation of Sholawat Da'wah Dhikr carries out in a way, the strategy is carried out by providing religious guidance, improving the quality and quantity of its members, carrying out interalization relationships between the management and its members, maintaining the attitude and behavior of activists, increasing social activities towards the community, developing types of activities and providing supporting infrastructure. The strategy carried out by Sholawat Da'wah Dhikr is a good and mature strategy to increase the social and religious activities of the community.